Molecular Structure and Polymorphism of Microsatellite Loci of Caucasian Rock Lizards Darevskia raddei of the “Yerevan” Population from Armenia - Martirosyan, I. A.; Valyaeva, A. A.; Arakelyan, M. S.; Ryskov, A. P. (Russian journal of genetics, 2022)
The analysis of polymorphism of microsatellite loci of Darevskia raddei “Yerevan” population allowed us to establish that the population of D. raddei “Yerevan” belongs to the subspecies Darevskia raddei nairensis .